Brill's New Jacoby (Jacoby online, 2007)
Brill's New Jacoby is a fully-revised and enlarged edition of Jacoby’s Die Fragmente der Griechischen Historiker I-III, providing new texts of the ancient historians in many instances as well as several new historians and many new fragments of existing historians that were either unknown to Jacoby or excluded by him. Brill’s New Jacoby, Second Edition (BNJ2) is a revised and enlarged edition of Brill’s New Jacoby (BNJ). Like Brill’s New Jacoby, this revised edition has texts and historians not included in Jacoby’s Die Fragmente der Griechischen Historiker I-III.
Gesamttitel bis 2021: BrillOnline reference works
Gesehen am 23.01.2023
Keywords: Datenbank; Quelle; Fragment; Geschichtsschreibung; Griechenland; Griechisch